Tackling a global epidemic threat: Nipah surveillance in Bangladesh, 2006–2021 - Satter, Syed Moinuddin; Aquib, Wasik Rahman; Sultana, Sharmin; Sharif, Ahmad Raihan; Nazneen, Arifa; Alam, Muhammad Rashedul; Siddika, Ayesha; Akther Ema, Fateha; Chowdhury, Kamal Ibne Amin; Alam, Ahmed Nawsher; Rahman, Mahmudur; Klena, John D.; et al. (PLOS Neglected Tropical Diseases, 2023)
Author summary NiV is one of the most fatal emerging bat-borne zoonotic viruses, posing a threat to global health security. Since the first recognized outbreak in Bangladesh in 2001, human infections have been detected almost every year. In 2006, a hospital-based Nipah sentinel surveillance was established in Bangladesh for the early detection of cases and rapid response to outbreaks. Currently, this surveillance is running at ten strategically chosen public hospitals throughout Bangladesh. Till December 2021, a total of 322 Nipah cases have been reported in Bangladesh, 71% of whom has died during the course of infection. Throughout the years, fever, vomiting, headache, fatigue, and increased salivation have remained the most commonly observed symptoms. Half of the reported cases were primary cases (162/322) having an established history of consuming raw date palm sap (DPS) or tari, and 29% were infected through person-to-person transmission. Since the inception of surveillance, there has been a decrease in large outbreaks and a concurrent increase in sporadic Nipah case detection throughout the country. The overall epidemiology of Nipah virus infection in Bangladesh has remained consistent throughout the years. National Nipah surveillance of Bangladesh is the only global, systematic surveillance to detect human NiV infection. The findings from this surveillance have contributed to the early detection of Nipah cases, understanding of disease epidemiology, and implementation of timely public health interventions for the prevention and containment of human NiV infection.